2010
DOI: 10.1089/lap.2009.0438
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Different Energy-Based Vascular Sealing Systems for the Hemostasis of Various Types of Arteries: A Porcine Model—Evaluation of Ligasure ForceTriad™

Abstract: Both the LSAt and LSAtFT secured all vessel sizes to well above physiologic levels. The LSAtFT could be used more confidently in vessels up to 7 mm. Our findings indicate that LSAtFT could be a safer and more efficient instrument for advanced laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
1
12
0
2
Order By: Relevance
“…The use of vessel‐sealing devices (VSD) in laparoscopic surgery allows for rapid vascular sealing and tissue division, eliminating the requirement for surgical clips or ligatures . Vessel‐sealing devices use an energy platform to measure tissue impedance and direct the handset to apply high‐current/low‐voltage energy for tissue fusion . The applied energy denatures collagen and elastin within vessel walls, resulting in crosslinking of denatured proteins to form a vascular seal in vessels up to 7 mm in diameter .…”
Section: Introductionmentioning
confidence: 99%
“…The use of vessel‐sealing devices (VSD) in laparoscopic surgery allows for rapid vascular sealing and tissue division, eliminating the requirement for surgical clips or ligatures . Vessel‐sealing devices use an energy platform to measure tissue impedance and direct the handset to apply high‐current/low‐voltage energy for tissue fusion . The applied energy denatures collagen and elastin within vessel walls, resulting in crosslinking of denatured proteins to form a vascular seal in vessels up to 7 mm in diameter .…”
Section: Introductionmentioning
confidence: 99%
“…The energy platform (ForceTriad; Covidien Medtronic) measures tissue impedance and emits a sound cue when tissue impedance rises and the tissue is coagulated. This signals the surgeon to cut the vessel with the blade contained within the device hand piece, which positions the cut at the center of the formed seal . The device can provide permanent occlusion of vascular structures of up to 7 mm in diameter on each side of the cut .…”
Section: Introductionmentioning
confidence: 99%
“…The authors used a single electrosurgical generator and a single monopolar instrument in the study, and reported that V mode did not reduce the depth of thermal tissue spread compared with conventional continuous/interrupted waveforms [7]. The same advanced bipolar instrument (LigaSure Atlas TM ) was connected to 2 different ESUs (LigaSure TM Vessel Sealing unit and ForceTriad TM unit) in another study and the “vessel sealing” speed and lateral thermal spread were found to be statistically significant between the 2 ESUs [25]. Our study demonstrated that ESU used with monopolar systems and continuous/interrupted waveforms provided statistically significant results in terms of lateral thermal spread.…”
Section: Discussionmentioning
confidence: 99%